APLIKASI WORDWALL DALAM MENINGKATKAN MOTIVASI BELAJAR: ANALISIS PEMBELAJARAN PANCASILA DI LAB SCHOOL UNIVERSITAS PGRI SEMARANG - Azziyah, Azimatun Nor; Suneki, Sri; maryanto, Maryanto (FPIPSKR Universitas PGRI Semarang, 2024)
This research is motivated by the finding that teachers are less than optimal in managing learning which contains minimum standards regarding the learning process that must be carried out. This is evidenced by a differentiated learning process, which is learning as recommended in the Merdeka Curriculum which is regulated in policy Number 56 / M / 2022 concerning Guidelines for Curriculum Implementation in the Context of Learning Recovery. The purpose of this study was to determine the implementation of the Merdeka Curriculum in terms of process standards in learning Pancasila Education class VII SMP Negeri 10 Semarang. This research uses qualitative descriptive research methods. The results showed that the implementation of the Merdeka Curriculum in terms of process standards in learning Pancasila Education class VII SMP Negeri 10 Semarang, namely in lesson planning, the teacher compiles teaching modules that fulfill the components available in the learning and assessment guidebook published by the standards, curriculum, and educational assessment agency of the ministry of education, culture, research, and technology. The teacher's learning implementation predominantly uses the problem-based learning method compared to the differentiated learning method which is a recommended learning method in the independent curriculum. Meanwhile, learning assessment is that teachers use class assessments which include formative and summative assessments. Formative assessment is carried out during the End of Semester Assessment (PAS) and summative assessment is carried out when learning in the classroom is carried out.